Leismanicidal Activity of Propolis Collected in the Semiarid Region of Brazil - Giani Maria Cavalcante; Celso Amorim Camara; Eva Monica Sarmento Da Silva; Mariana Silva Santos; Anderson Brandão Leite; Aline Cavalcanti Queiroz; Aline Cavalcanti Queiroz; Amanda Evelyn Da Silva; Morgana Vital Araújo; Magna Suzana Alexandre-Moreira; Tania Maria Sarmento Silva (Frontiers in Pharmacology, 2021)
Objective: The aim of the current study is to investigate the chemical composition, cytotoxic effect, and leishmanicidal activity of propolis collected in the semi-arid region of Bahia, Brazil.Methods: EtOH extract, hexane, EtOAc and MeOH fractions from propolis were analyzed by ultra-performance liquid chromatography coupled with diode array detector and quadrupole time-of-flight mass spectrometry. The identification was based on the exact mass, general fragmentation behaviors and UV absorption of the flavonoids. The in vitro cytotoxic effect and leishmanicidal activity of ethanolic extract, hexane, ethyl acetate, and methanolic fractions of propolis were evaluated.Results: Five triterpenes and twenty-four flavonoids were identified. The propolis did not present toxicity to the host cell up to the maximum concentration tested. In addition, all tested samples showed statistically significant activity against promastigotes of Leishmania chagasi and Leishmania amazonensis. Regarding the activity against amastigote forms of L. amazonensis, the hexane fraction, presented statistically significant activity with IC50 of 1.3 ± 0.1 μg/ml.Conclusion: The results support the idea that propolis can be used for future antileishmania studies.